Five-year survival in patients with extensive-stage small cell lung cancer treated with atezolizumab in the Phase III IMpower133 study and the Phase III IMbrella A extension study - Reck, Martin; Dziadziuszko, Rafal; Sugawara, Shunichi; Kao, Steven; Hochmair, Maximilian; Huemer, Florian; de Castro, Gilberto; Havel, Libor; Bernabé Caro, Reyes; Losonczy, György; Lee, Jong-Seok; Kowalski, Dariusz M; et al. (Lung cancer, 2024)
OBJECTIVES: IMbrella A is a Phase III extension study that allowed rollover from Roche/Genentech-sponsored atezolizumab trials, including IMpower133, a Phase I/III trial of first-line atezolizumab or placebo plus carboplatin/etoposide in extensive-stage small cell lung cancer. We report outcomes from an exploratory analysis of IMpower133 with extended time-to-event data for patients who rolled over to IMbrella A. MATERIALS AND METHODS: IMpower133 patients could roll over to IMbrella A to receive atezolizumab 1200 mg intravenously every three weeks if they continued to receive atezolizumab at IMpower133 closure or were in survival follow-up after atezolizumab discontinuation. Overall survival and safety were assessed; only serious adverse events and AEs of special interest were collected in IMbrella A. RESULTS: Eighteen of 26 eligible patients rolled over to IMbrella A. At clinical cutoff (March 16, 2023), median follow-up in the atezolizumab plus carboplatin/etoposide arm (IMpower133 and IMbrella A) was 59.4 months. The three-, four-, and five-year overall survival (95 % CI) estimates were 16 % (11 %-21 %), 13 % (8 %-18 %), and 12 % (7 %-17 %), respectively. In IMbrella A, serious adverse events occurred in three patients (16.7 %), and one adverse event of special interest was reported (grade two hypothyroidism). CONCLUSION: This long-term analysis of patients from IMbrella A previously enrolled in IMpower133 provides the first report of five-year overall survival outcomes in patients with extensive-stage small cell lung cancer treated with first-line cancer immunotherapy and chemotherapy. While limited by small patient numbers and lack of long-term data for the IMpower133 control arm, exploratory overall survival analyses in patients treated with atezolizumab plus carboplatin/etoposide compared favorably with historical data with chemotherapy alone. NCT03148418.
Keywords: Neoplasm Staging; staging nádorů; následné studie; Survival Rate; Carboplatin; Etoposide; míra přežití; lidé; Antibodies, Monoclonal, Humanized; senioři nad 80 let; senioři; nádory plic; malobuněčný karcinom plic; humanizované monoklonální protilátky; mužské pohlaví; protokoly protinádorové kombinované chemoterapie; Female; Adult; Small Cell Lung Carcinoma; Male; Follow-Up Studies; ženské pohlaví; dospělí; Aged, 80 and over; etoposid; Aged; Humans; Antineoplastic Combined Chemotherapy Protocols; lidé středního věku; Middle Aged; karboplatina; Lung Neoplasms